Critical angioedema induced by a renin angiotensin system blocker in the contemporary era of increasing heart failure: A case report and commentary - Masafumi Sato; Masao Takahashi; Kazuomi Kario (The Journal of Clinical Hypertension, 2021)
Abstract Bradykinin‐mediated angioedema, a nonallergic reaction most commonly caused by renin angiotensin system (RAS) blockers, has the potential to lead to a critical condition. RAS blockers are important for treating heart failure and are widely used in clinical settings. We present the case of an 85‐year‐old man who was administered enalapril after percutaneous coronary intervention for an acute myocardial infarction and developed severe angioedema requiring a tracheostomy. He had multiple risks for angioedema including advanced age, smoking history, renal dysfunction, and longstanding use of an angiotensin receptor blocker. The prompt diagnosis of drug‐induced angioedema is critical and depends on physicians' recognition of risk factors and knowledge of pathophysiology. In the present era of increasingly prevalent heart failure, it is imperative that the possibility of angioedema receives attention, especially given the continuing reliance on RAS blockers and the advent of angiotensin receptor neprilysin inhibitors, a new type of heart failure drug.